ANALISIS FAKTOR PENYEBAB KECELAKAAN DALAM HUBUNGAN KERJA PT X BERDASARKAN TEORI LOSS CAUSATION MODEL (Studi Kasus Pada Karyawan Bagian Warehouse) - Santini Sekar Candra Sulistyawati; Ida Wahyuni; Daru Lestantyo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Accident on working relationship is something that nobody want, that take place outside the working place and causing disadvantage. PT X is a manufacturing company that produce diesel engine in Semarang. PT X has applied the golden flagged SMK3, but the case of accident especialy on working relations are still at high number. From 2015 to 2017, analysis trend shows an escalation on accident rate from 4 to 6 case of accident. The investigation data shows that the most involved on accident at working relations come from warehouse employees. This is a descriptive qualitative research with an in-depth interview. Main informan are 3 warehouse workers that already had accident at working relation and 2 warehouse workers that never had an accident at working relations before. The triangulation informan are the chief of warehouse, safety leader of warehose and K3 expert from PT X. The outcome from the research shows that the cause of accident to the warehouse workers are substandard acts, substandard conditions, personal factors, job factors, inadequate program and inadequate standard. Substandard acts mentioned above are riding behavior that doesn’t meet the standart, include talking while riding, daydreaming, haste, high speed riding, and careless overtaking. Substandard conditions mentioned above are the condition of the road are accident prone, narrow, wavy, perforated, sharp turn, slippery and muddy. Personal factors mentioned above are stress that comes from working situation and skill of braking the motorcycle. Job factors mentioned above are extra overtime work and the job demand that has to be accomplished when the production rate is high. Inadequate program that mentioned above is the driving practice in safety riding training program that still use a motorcycle simulator and hasnt been practiced on the suitable road conditions as passed by the workers. Inadequate standard that mentioned above is the unavailablelity of driving SOP in PT X.